COMPETITION MERGER REVIEW FOR CROSS-BORDER MERGERS AND ACQUISITIONS IN INDONESIA - Zulheri, Zulheri (UI Scholars Hub, 2017)
This article aimed at expressing ideas on a legal construction of competition merger review (CMR) on Crossborder Mergers and Acquisitions (CBM&A) that have Indonesian legal dimension. The problem has been triggered by the lack of CMR guidelines for CBM&A to nurture a fair and sustainable business competition (FSBC). Consequently, the existing guideline is inadequate for reviewing CBM&A proposals which have a multi-jurisdiction dimension character. As a result, merging (gigantic) companies doing business in Indonesia have enormous opportunities to engage in anti-competitive behavior in the domestic market. In its turn, it brings the impact of reducing competition itself whereby national companies become easily marginalized and find themselves in a vulnerable situation. To seek solutions to this problem, this research has been conducted through a normative approach, starting from the formulation of the problem up to an in-depth analysis and drawing conclusions. In order to achieve the said purpose, a literature study was conducted to explore and collect related law information on CBM&A, including CMR methods, namely: Market Dominance Test, Substantial Lessening of Competition/SLC Test, Public Interest Test, and four hybrid Tests: i) Hybrid Test One=SIEC Test; ii) Hybrid Test Two; iii) Hybrid Test Three; and Hybrid Test Four). Out of these seven methods of CMR, I consider to choose the SLC Test as the method for reviewing CBM&A proposal. At the end, this study concludes as follows: 1) there is an urgent need for CMR in the methods of SLC Test for cross-border merger and acquisition proposals in order to fill the absence of a merger review guideline that contains a multi-jurisdiction dimension and to nurture a fair and sustainable business competition in Indonesia; 2) the substantive norms for constructing CMR in the methods of SLC Test for CBM&A transactions in Indonesia should take into account the national law regime: company law, merger law, investment law including the existing public interest. In addition to that, the principles of certainty, efficiency, transparency, and proportionality should also be considered. Thus, I recommend to enact a SLC Test Guideline in order to strengthen the legal review of CBM&A proposals for supporting FSBC, to maintain dynamic, secure, and stable national economy and development.